Potensi Ekowisata Air Panas Di Negeri Nalahia Pulau Nusalaut Kabupaten Maluku Tengah - Tambunan, Nover; Lelloltery, Henderina; Seipalla, Billy B (MAKILA, 2023)
This study aimed to determine the potential for hot spring ecotourism in Nalahia village on Nusalaut Island, Central Maluku Regency. The method used is direct observation (survey method). Data was collected on all-natural tourist attractions through fauna data around hot springs. Tourist data collection is done by conducting interviews using a questionnaire for tourists with accidental sampling. Data were analyzed using descriptive analysis of tourism potential in hot springs attractions and tourists visiting Nalahia hot springs. The results showed that hot water attractions in Nalahia country are found in two places, namely "Bantang" hot springs around the sago forest and hot springs on the beach known as "kerkof" hot springs with different temperatures between 38 ̊C to 43 C. Tourist activities that are often carried out by tourists are bathing and bathing, enjoying the natural scenery, taking pictures and research. The object hot spring tourism attraction in Negeri Nalahia, based on the results of interviews with tourists, is the main activity tourists carry out. The results of discussions related to tourist perceptions of hot spring attractions, 90% of tourists stated that the Nalahia hot spring tourist attraction has attractiveness and beautiful natural scenery, so many tourists think they want to return to Nalahia country, while facilities are limited, a suggestion from tourists to be able to carry out the construction of facilities around the hot spring tourist area. Community participation in the Nalahia hot spring tourism activities involves ideas, human power, and expertise.